Endogenous coalition formation in global pollution control - Michael Finus; Bianca Rundshagen (Fondazione Eni Enrico Mattei (FEEM), 2001)
We extend the work on coalition formation in global pollution control by allowing for multiple coalitions. Equilibrium coalitions are derived under different
Keywords: C72; Q20; 330; International environmental agreements; coalition formation games; global pollution; Umweltabkommen; Internationale Umweltpolitik; Verhandlungstheorie; Koalition; Theorie